2020
DOI: 10.1186/s13020-020-00392-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the mechanism of Yuzhi Zhixue granule on ovulatory dysfunctional uterine bleeding by network pharmacology and molecular docking

Abstract: Background Yuzhi Zhixue Granule (YZG) is a traditional Chinese patent medicine for treating excessive menstrual flow caused by ovulatory dysfunctional uterine bleeding (ODUB) accompanied by heat syndrome. However, the underlying molecular mechanisms, potential targets, and active ingredients of this prescription are still unknown. Therefore, it is imperative to explore the molecular mechanism of YZG. Methods The active compounds in Y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…There are some problems such as poor compliance during treatment and easy recurrence after treatment. Other studies have indicated that, long-term oral hormone drugs increased the incidence of cardiovascular and cerebrovascular diseases, endometrial cancer, and breast cancer to a certain extent [ 15 ]. The perimenopausal AUB-O patients with poor effect of repeated drugs and conservative treatment finally need to choose surgical hysterectomy, but conventional hysterectomy has some problems, such as trauma, long recovery period, operation, and postoperative complications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some problems such as poor compliance during treatment and easy recurrence after treatment. Other studies have indicated that, long-term oral hormone drugs increased the incidence of cardiovascular and cerebrovascular diseases, endometrial cancer, and breast cancer to a certain extent [ 15 ]. The perimenopausal AUB-O patients with poor effect of repeated drugs and conservative treatment finally need to choose surgical hysterectomy, but conventional hysterectomy has some problems, such as trauma, long recovery period, operation, and postoperative complications [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…To improve the accuracy of the connection between small molecular compounds and the core target proteins, we used molecular docking to evaluate the interactions between compounds and target proteins. It is generally believed that when the binding energy of a ligand and receptor is <−4 kcal/mol, there is potential binding activity between the ligand and receptor [ 35 ]. A binding energy score less than −5 kcal/mol suggests strong binding between the ligand and receptor [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because beta-carotene has no free hydrogen bond, it cannot stably bind to the target through hydrogen bond, so it is eliminated. It is generally believed that when the binding energy of ligand and receptor is <−4 kcal/mol, there is potential binding activity between them; binding energy <−5 kcal/mol suggests a significant binding ability between them [ 32 ]. Our docking results showed that the binding energy of the receptor proteins and the active ingredients were all lower than −5 kcal/mol, indicating that the receptor proteins and the active ingredients were well bound, which further provides evidence support for TDXD treatment of HF ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%